2010
DOI: 10.1002/icd.703
|View full text |Cite
|
Sign up to set email alerts
|

Early indications of delayed cognitive development in preschool children born very preterm: evidence from domain‐general and domain‐specific tasks

Abstract: Cognitive impairment often follows preterm birth but its early underlying nature is not well understood. We used a novel approach by investigating the development of colour cognition in 54 very preterm children born p30 weeks gestational age without severe neurosensory impairment and 37 age-matched term-born controls, aged 2-5 years. Quantitative and qualitative differences in the development of colour cognition are well charted throughout the preschool years, enabling delayed from deviant development to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…In relation to cognitive development, the research found global cognitive delays in children born prematurely, but the specific cognitive processes most affected are memory from 2 to 6 years (40,42,43,45,47,48,52), attention from the first year of birth (35,36,38,41,44) and visual-spatial processing at 3-4 years (42,43,45). However, there is no consensus on the degree of impairment of memory and executive function, because some studies find they are not affected in the first 2 years (37), and other studies find worse scores at 5 and 6 years (48, 52).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to cognitive development, the research found global cognitive delays in children born prematurely, but the specific cognitive processes most affected are memory from 2 to 6 years (40,42,43,45,47,48,52), attention from the first year of birth (35,36,38,41,44) and visual-spatial processing at 3-4 years (42,43,45). However, there is no consensus on the degree of impairment of memory and executive function, because some studies find they are not affected in the first 2 years (37), and other studies find worse scores at 5 and 6 years (48, 52).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no conclusive data about problems in expressive and receptive language develop-ment in general, vocabulary size and communication skills. Some studies found that preterm children have problems in expressive and receptive language development in general in the first two years of life, and from 2 to 6 years of age (40,48,52,54,61,62,65). One study found that preterm children have no problems in expressive and receptive language development in general at 5 years (63) and other study found that these children have problems in some specific components of expressive language (sentences), but they do not have problems in other components (information) at 3 years old (60).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations